Evaluation of extracellular signal regulated kinase 1 expression in premalignant lesions of oral cavity - Yadav, Manisha; Arora, Vipin; Hussain, Showket; Sisodiya, Sandeep; Diwaker, Preeti; Goyal, Ashish; Taneja, Harish C. (International Surgery Journal, 2020)
Background: Most oral squamous cell carcinomas are preceded by premalignant lesions like leukoplakia, erythroplakia etc. Identification of these lesions by molecular markers and intervention at an early stage can reduce mortality, morbidity and cost of treatment associated with oral cancer. Extracellular signal regulated kinase 1 (ERK 1) is one of the various markers involved in carcinogenesis. Methods: We studied the expression of ERK 1 in twenty-five oral premalignant lesion biopsies using immunohistochemistry (IHC) and western blot analysis. Results: Ninety-two percent of premalignant lesions showed positive expression of ERK 1 on IHC and the same were confirmed by western blot analysis. ERK 1 expression was increased in premalignant lesions as compared to peripheral normal tissue but the difference between them was not statistically significant. On comparing the level of expression of peripheral normal and premalignant tissue on IHC, moderate and high level of expressions were significantly higher in premalignant lesions (24%) than peripheral normal tissue (12%). Conclusions: There was an increased expression of ERK 1 in oral premalignant lesions as compared to peripheral normal tissue, although, this difference was not statistically significant.